Adaptation and coordinated evolution of plant hydraulic traits. (18th August 2020) - Sanchez‐Martinez, Pablo; Martínez‐Vilalta, Jordi; Dexter, Kyle G.; Segovia, Ricardo A.; Mencuccini, Maurizio
Abstract: Hydraulic properties control plant responses to climate and are likely to be under strong selective pressure, but their macro‐evolutionary history remains poorly characterised. To fill this gap, we compiled a global dataset of hydraulic traits describing xylem conductivity ( K s ), xylem resistance to embolism (P50), sapwood allocation relative to leaf area (Hv) and drought exposure (ψmin ), and matched it with global seed plant phylogenies. Individually, these traits present medium to high levels of phylogenetic signal, partly related to environmental selective pressures shaping lineage evolution. Most of these traits evolved independently of each other, being co‐selected by the same environmental pressures. However, the evolutionary correlations between P50 and ψmin and between K s and Hv show signs of deeper evolutionary integration because of functional, developmental or genetic constraints, conforming to evolutionary modules. We do not detect evolutionary integration between conductivity and resistance to embolism, rejecting a hardwired trade‐off for this pair of traits. Abstract : We compiled a global dataset of hydraulic traits describing xylem conductivity ( K s ), xylem resistance to embolism (P50), sapwood allocation relative to leaf area (Hv) and drought exposure (ψmin ), and matched it with global seed plant phylogenies. Individually, these traits present medium to high levels of phylogenetic signal, partly related to environmental selective pressures shaping lineage evolution. Most of these traits evolved independently of each other, being co‐selected by the same environmental pressures. However, the evolutionary correlations between P50 and ψmin and between K s and Hv show signs of deeper evolutionary integration because of functional, developmental or genetic constraints, conforming to evolutionary modules. We do not detect evolutionary integration between conductivity and resistance to embolism, rejecting a hardwired trade‐off for this pair of traits.